Pengaruh Ukuran Perusahaan, Jenis Opini Auditor, Laba/Rugi Operasi, Profitabilitas dan Solvabilitas Terhadap Audit Delay Sub Sektor Rokok yang Terdaftar di Bursa Efek Indonesia - setiono, hari; Rubiyanto, Rubiyanto (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Financial statements can be said to be relevant if the delivery is timely. This timeliness can be seen from audit delay, namely the length of reporting of financial statements between the closing date of the book until the date of the auditor's report. The purpose of this study was to determine the effect of company size variables, auditor opinion types, operating profit/loss, profitability, and solvency levels, on audit delay in cigarette companies listed on the Indonesia Stock Exchange in 2011-2017. This type of research is a qualitative descriptive. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) by taking financial statement data. The analysis method uses multiple linear regression analysis. The results obtained in this study indicate that simultaneously the five variables have a significant effect of 42% on audit delay. And partially from the 5 variables that affect audit delay is the level of profitability with a significance value of t 0.018 which is less than 0.5%, while the others have no effect.